Camp TV : Trans Gender Queer Sitcom History - Miller, Quinlan, 1981- (Book collections on Project MUSE., 2019)
Quinlan Miller reframes American television history by tracing a camp aesthetic and the common appearance of trans queer gender characters in both iconic and lesser known sitcoms throughout the 1950s and 1960s.